Estudo do potencial paratransgênico de bactérias cultiváveis associadas ao Anopheles darlingi Root,1926, para controle da malária - Correa, Laura Viana (2019)
Malaria is a serious parasitic disease that affects millions of people across the planet. It is caused by protozoa of the genus Plasmodium and transmitted to humans by the bite of the infected female Anopheles mosquitoes. Although conventional vector control strategies have reduced the burden of disease, for some time malaria has grown in recent years, requiring more effective methods to control it. A promising alternative for malaria control is paratransgenesis, which uses genetically engineered symbiont bacteria to express anti-plasmodium proteins and reinserted into mosquitoes to inhibit or kill Plasmodium within the vector. However, for the success of this alternative it is important that the right candidate has some indispensable characteristics, such as being a symbiote of the vector, being cultivable and susceptible to genetic manipulation, remaining stable after transformation and being transferred at all stages of mosquito development. Transestadial transmission, where the larval stage is transferred to the adult mosquito, is a very important criterion for paratransgenesis. For it is in the immature stages that mosquitoes acquire most of their bacterial microbiota and the symbiote survives metamorphosis and colonizes the midgut gut, where the most vulnerable stages of Plasmodium development occur, would be a strong candidate for use in this approach. Thus, this work aimed to select cultivable bacteria, which present characteristics of trans-state transmission in Anopheles darlingi, the main vector of malaria in the Amazon region, for use in future paratransgenic approaches. By bacterial isolation, morphological characterization, molecular identification by the 16S rRNA gene of bacterial species associated with larvae, pupae and adults of A. darlingi and genetic transformation test for similar bacteria present in these stages of development. The following results were obtained: 166 bacteria were isolated and characterized morphologically, among them, 72 were identified and belonging to the Phylobacteria, Firmicutes Actinobacteria and Bacteroidetes. Twenty genera were also identified, predominantly Bacillus and Klebsiella, from which 38 different species were identified, and three species are strong candidates for paratransgenesis: Pantoea agglomerans, Pantoea dispersa and Enterobacter asburiae. Then they were selected for bacterial transformation test, with plasmid pKS1-GFP, Pantoea agglomerans was susceptible of genetic transformation, then it was monitored in the developmental stages of A.darlingi, presenting transestadial transmission capacity. Keywords: Malaria, Symbiont Bacteria, Transstadial Transmission and Paratransgenesis.